NORMAL COMPONENT OF CRITICAL CUTTING FORCE IN FIXED AND FREE SHREDDING OF THICK-STALK CROPS BY DISK SHREDDER BLADES - Alexander К. Fokeyev; Igor A. Budashov (Advanced Engineering Research)
Impact of three different blades on the normal component of the critical cutting force is considered. The formula of the critical force normal component as a result of the knurled blade operation is presented. The formula derivation of the critical force normal component in the fixed and free shredding is described.